HA Antibody-Mediated FcγRIIIa Activity Is Both Dependent on FcR Engagement and Interactions between HA and Sialic Acids - Cox, Freek; Kwaks, Ted; Brandenburg, Boerries; Koldijk, Martin H.; Klaren, Vincent; Smal, Bastiaan; Korse, Hans J. W. M.; Geelen, Eric; Tettero, Lisanne; Zuijdgeest, David; Stoop, Esther J. M.; Saeland, Eirikur; et al. (Frontiers in Immunology, 2016)
Interactions with receptors for the Fc region of IgG (FcγRs) have been shown to contribute to the in vivo protection against influenza A viruses provided by broadly neutralizing antibodies (bnAbs) that bind to the viral hemagglutinin (HA) stem. In particular, Fc-mediated antibody-dependent cellular cytotoxicity (ADCC) has been shown to contribute to protection by stem-binding bnAbs. Fc-mediated effector functions appear not to contribute to protection provided by strain-specific HA head-binding antibodies. We used a panel of anti-stem and anti-head influenza A and B monoclonal antibodies with identical human IgG1 Fc domains and investigated their ability to mediate ADCC associated FcγRIIIa activation. Antibodies which do not interfere with sialic acid binding of HA can mediate FcγRIIIa activation. However, the FcγRIIIa activation was inhibited when a mutant HA, unable to bind sialic acids, was used. Antibodies which block sialic acid receptor interactions of HA interfered with FcγRIIIa activation. The inhibition of FcγRIIIa activation by HA head-binding and sialic acid receptor blocking antibodies was confirmed in plasma samples of H5N1 vaccinated human subjects. Together, these results suggest that in addition to Fc–FcγR binding, interactions between HA and sialic acids on immune cells are required for optimal Fc-mediated effector functions by anti-HA antibodies.